2007
DOI: 10.1111/j.2007.0018-0661.01969.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic diversity of Guizotia abyssinica from Ethiopia using inter simple sequence repeat markers

Abstract: Within and among population genetic diversity of 37 Guizotia abyssinica populations from Ethiopia were analyzed using inter simple sequence repeats (ISSRs). Five primers amplified a total of 118 genomic DNA fragments across a total of 370 individuals of which 106 were polymorphic (89.83%). The average number of polymorphic bands per primer was 21.2. More bands were generated by primer UBC 888 (BDB(CA)(7.) The total genetic diversity (Ht) and the coefficient of genetic differentiation (Gst) were 0.4115 and 0.09… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…ISSRs provide extremely useful data for estimating genetic diversity (Ge et al 2005;Nan et al 2003;Petros et al 2007;Gomes et al 2009;Vargas-Ponce et al 2009), phylogenetic analyses (Matos et al 2001;Mort et al 2003;Wolfe and Randle 2001) for studying the inter-and intraspecific relations among plants (Archibald et al 2006;Petros et al 2008;Wolfe and Randle 2001). The objective of the present study was to determine whether ISSR markers provide sufficient resolution for interspecific discrimination of Mexican species of Physalis and to assess their utility for inferring interspecific relationships.…”
Section: Introductionmentioning
confidence: 99%
“…ISSRs provide extremely useful data for estimating genetic diversity (Ge et al 2005;Nan et al 2003;Petros et al 2007;Gomes et al 2009;Vargas-Ponce et al 2009), phylogenetic analyses (Matos et al 2001;Mort et al 2003;Wolfe and Randle 2001) for studying the inter-and intraspecific relations among plants (Archibald et al 2006;Petros et al 2008;Wolfe and Randle 2001). The objective of the present study was to determine whether ISSR markers provide sufficient resolution for interspecific discrimination of Mexican species of Physalis and to assess their utility for inferring interspecific relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Inter Simple Sequence Repeat analysis of G. abyssinica populations collected from eight niger growing regions of Ethiopia was done by Petros et al (2007). It was shown that the technique reveals high polymorphism within and among the niger populations of Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the genetic diversity of Ethiopian niger using various molecular marker techniques have revealed high genetic variation (e.g., Geleta et al 2007Geleta et al , 2008Petros et al 2007). Interesting genotypes with different desirable traits have recently been identified and are being developed in our department.…”
Section: Introductionmentioning
confidence: 98%